Menggali Makna Identitas Nasional :Cerminan dan Jati diri Bangsa - Muhammad Fadhel; Abdul Rahman Bintang; Sasmi Nelwati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
National identity is a complex and important concept for a nation. National identity reflects the identity of a nation and is a marker of a country's existence in the international world. This national article will dig deeper into the meaning of national identity, how national identity reflects national identity, and why identity has a crucial role in building national pride and unity. In this article, we will dig deeper into the meaning of national identity as a reflection and identity of the nation. National identity can be seen as a reflection of a nation because it reflects the characteristics of that nation. National identity includes language, customs, arts and culture, history, and beliefs held by society. Through national identity, people can recognize themselves and differentiate themselves from other nations.